2011
DOI: 10.1002/ejoc.201001538
|View full text |Cite
|
Sign up to set email alerts
|

Developments in Chiral Binaphthyl‐Derived Brønsted/Lewis Acids and Hydrogen‐Bond‐Donor Organocatalysis

Abstract: Keywords: Organocatalysis / Brønsted acids / Lewis acids / Hydrogen bonds / Binaphthyl derivativesIn recent years, binaphthyl compounds have found frequent applications in the design of various asymmetric organocatalysts, because binaphthyl structures are an attractive platform for organocatalyst development, particularly in light of their axial chirality characteristic. In this review, we discuss

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(34 citation statements)
references
References 69 publications
0
34
0
Order By: Relevance
“…They are readily available from commercial suppliers. In addition to their use as chiral ligands for enantioselective synthesis, enantiopure BINOL is also an excellent reagent for optical resolutions via formation of host–guest complexes, and its use has been reported as NMR CSA for sulfoxides, selenoxides, and some important drugs . From the NMR point of view, BINOL is advantageous as all their signals lie in the aromatic zone of the spectrum, so leaving free of interference the whole aliphatic range of substrate resonances.…”
Section: Resultsmentioning
confidence: 99%
“…They are readily available from commercial suppliers. In addition to their use as chiral ligands for enantioselective synthesis, enantiopure BINOL is also an excellent reagent for optical resolutions via formation of host–guest complexes, and its use has been reported as NMR CSA for sulfoxides, selenoxides, and some important drugs . From the NMR point of view, BINOL is advantageous as all their signals lie in the aromatic zone of the spectrum, so leaving free of interference the whole aliphatic range of substrate resonances.…”
Section: Resultsmentioning
confidence: 99%
“…Related studies in these laboratories had demonstrated that Lewis base catalyzed seleno, thio and bromocycloetherification are greatly accelerated by the addition of a stoichiometric amount of an achiral Brønsted acid. The pK a and general applicability of chiral phosphoric acids made them attractive candidates for the development of an enantioselective bromocycloetherification process using a catalytic amount of a chiral Brønsted acid, potentially in conjunction with a Lewis base co‐catalyst . This line of research led to the development of an enantioselective bromocycloetherification reaction of 5‐arylpentenols ( 1a , 1d , 1e , 1f , 1g , 1h , 1i , 1j , 1k , 1l , 1m ) cooperatively catalyzed by the combination of the versatile chiral phosphoric acid TRIP ( 2a ) and the achiral Lewis base Ph 3 P=S, producing chiral tetrahydrofurans ( 3a , 3d , 3e , 3f , 3g , 3h , 3i , 3j , 3k , 3l , 3m ) and tetrahydropyrans ( 4a , 4d , 4e , 4f , 4g , 4h , 4i , 4j , 4k , 4l , 4m ) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[183][184][185][186][187] There are three modes of activation of carbonyl compounds ( Figure 14): (1) Brønsted acid catalysis 351, (2) double hydrogen bonding 352, and (3) single hydrogen bonding 353. It is of note, however, that there is no clear distinction between Brønsted acid catalysis and hydrogen-bond catalysis.…”
Section: Brønsted Acid and Hydrogen-bond Catalysismentioning
confidence: 99%